Pengawasan Orang Tua Dalam Penggunaan Gadget Pada Anak Usia Dini Selama Masa Pandemi COVID-19 - Cau Kim Jiu; Kharisma Pratama; Jaka Pradika; Hartono Hartono; Indri Erwhani (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
Changes in the learning process during the pandemic from classroom learning to online learning certainly cannot be separated from the role of gadgets, but for early childhood the online learning process using gadgets needs to get supervision from parents to minimize negative impacts. This study aims to explore the way parents monitor the use of gadgets during the Covid-19 pandemic in early childhood aged 4-6 years at Aisyiyah Kindergarten Bustanul Athfal 6 Pontianak City. This research is a qualitative research. Data were obtained through in-depth interviews and Focus Group Discussions. Participants in this study consisted of 10 mothers who had early childhood. There are 4 themes found in this study, namely 1) managing the time of using gadgets, 2) limiting access, 3) giving passwords to gadgets and 4) giving rewards and punishments. This study concludes that to reduce the negative impact and addiction to gadgets, parental supervision is needed in the use of gadgets.